Diskursus Sunnah Tasyri’iyyah dan Non-Tasyri’iyyah: Telaah Perspektif Yusuf Al-Qardhawi - Naylul ‘Izzah Walkaromah; Dhiya’ Ramadhani (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
This article discusses the discourse of sunnah tasyri'iyyah and non-tasyri'iyyah sunnah from the perspective of Yusuf al-Qardhawi. Al-Qardhawi is an intellectual who gives full attention to the study of sunnah. In addition to carrying the responsibility as a Messenger, the Prophet Muhammad is a human being who has physical and spiritual needs as humans in general. This highlights some of the prophet's actions that are important to classify according to the prophet's capacity as a messenger of God and the prophet's capacity as an ordinary human being. The understanding of the classification of sunnah tasyri'iyyah and non-tasyri'iyyah becomes a significant thing to be explored further because there are some tendencies in generalizing the sunnah so as to collect all the sunnah of the prophet as sunnah that is bound by sharia. This article is classified as qualitative research and uses literature review as a reference in collecting and analyzing data. It can be concluded that according to Yusuf al-Qardhawi, sunnah tasyri'iyyah is a sunnah with a sharia dimension that comes from the Prophet Muhammad as a Messenger, while non-tasyri'iyyah sunnah is a prophet's sunnah that does not contain demands to be practiced or followed and is conditional and temporary. The criteria for non-tashri'iyyah sunnah are; 1) actions and words of the Prophet based on experiments (worldly aspects), 2) actions and words of the Prophet as head of state and judge, 3) commands and prohibitions of the Prophet that contain recommendations, 4) pure actions of the Prophet, 5) actions of the Prophet as a human being. When addressing the sunnah as sharia two contradictory groups emerged; al-Ghullah and al-Muqashirun. In response to both groups al-Qardhawi moderate.